5th Aircraft Structural Design Conference : conference programme & proceedings, 4-6, October 2016. (Royal Aeronautical Society, 2016)
The Royal Aeronautical Society's 5th Aircraft Structural Design Conference, undertaken with the support of the University of Manchester, will address the challenges facing the designers of the next generation of aircraft. These arise because the new designs will need to meet strict environmental constraints and will be subject to ever increasing pressures for reductions in manufacturing and life-cycle costs and continual improvements in overall performance/efficiency factors. The resulting aircraft will be complex, requiring multi-disciplinary design approaches and solutions in a distributed design environment.
Keywords: Airframes -- Design and construction.; elektronické knihy; electronic books